Senior high school and the labor market: Perspectives of grade 12 students and human resource officers - Aniceto C. Orbeta; Marites B. Lagarto; Ma. Kristina P. Ortiz; Danica Aisa P. Ortiz; Maropsil V. Potestad (Philippine Institute for Development Studies (PIDS), 2018)
The enactment of RA 10533 or the Enhanced Basic Education Act of 2013 added two years to basic education. One of the rationales offered by proponents of the law is that Senior High School (SHS) graduates can work or engage in entrepreneurial activities if they choose to do so. This study assesses the likelihood of achieving the employment and entrepreneurship objectives of the program by examining the experience of grade 12 graduating students and the views of firms about the labor market prospects of the SHS graduates. It does this by (i) looking into the SHS curriculum and the competencies developed, (ii) identifying the types of jobs that fit the Grade 12 graduates, (iii) gathering the private sector perspective on the jobs available and appropriate for the Grade 12 graduates, and (iv) providing policy recommendations for the improvement of the implementation of the SHS program. The study revealed the despite identifying employment and entrepreneurship as a rationale for the program, three quarters of the grade 12 students plan to proceed to higher education. This proportion is true even for those in the TVL track. Among the highlights of the FGD with students is the revelation that they are not very confident that they will get a job after graduating from SHS. Even for those who passed National Certifications assessments, they still believe the firms will prefer to hire college graduates over them. From the firm side, most of them lack in-depth knowledge of the SHS program. They expressed the need to be exposed to the SHS graduates before they can be confident in hiring them. While it may be too early to be gauging the performance of the SHS program particularly the performance of its graduates in the labor market, the study has uncovered areas for improving the implementation of the program to boost the chances of achieving the employment and entrepreneurship objectives.
Keywords: 330; Senior High School; K to 12; Basic Education; Labor Market